'Everyone is always learning': Case study of a Suzuki-inspired preschool. (1st June 2019) - Hendricks, Karin S.; Bucci, Madeline G.
The Suzuki violin method was originally envisioned as a universal approach to talent education, applicable to any field. Currently, however, the approach is limited primarily to music learning settings, with only a few exceptions in general education. The purpose of this study was to observe the activities and teacher‐child interactions in one preschool in which the Suzuki philosophy was implemented for general education in a holistic manner. We further considered how the co-equal integration of music with other educational content might be applicable in formal early childhood learning settings. Data collection included (1) observations of lessons and social interactions between students, teachers and administrators; (2) interviews with administrators and teachers and (3) review of preschool-related artefacts. We coded and analysed data according to five tenets of the Suzuki approach (i.e. every child can learn, group-based instruction, parent involvement, sensitive listening, prioritizing personal character over ability). Findings highlight specific ways in which teachers and administrators interpreted and adhered to these tenets in music and general education contexts, as well as potential areas for improvement and expansion. An emergent theme, 'everyone is always learning', encompassed the five tenets holistically, while also representing a general disposition among administrators and teachers to engage in preschool activities with a collective sense of gratitude and wonderment. This theme evokes the possibility of further research into the ways in which Suzuki teachers act as compassionate co-learners.